Acute Silica Exposure Triggers Pulmonary Inflammation Through Macrophage Pyroptosis: An Experimental Simulation - Yin, Haoyu; Fang, Lei; Wang, Lifeng; Xia, Yu; Tian, Jiaqi; Ma, Lan; Zhang, Jing; Li, Ning; Li, Weixiu; Yao, Sanqiao; Zhang, Lin (Frontiers in Immunology, 2022)
Silica is an essential substrate of various materials, and inhaling silica induces pulmonary diseases potentially associated with macrophage pyroptosis. Utilizing silica of micro- and nano- sizes, we explored the role of macrophage pyroptosis in silica-induced pulmonary inflammation. Under the transmission electron microscopy, we found that the internalization of silica nanoparticle induced membrane rupture and increased the number of intracellular vacuoles, and both sizes of silica could suppress cell viability and proliferation. Also, silica-exposed macrophages generated higher levels of ROS, together with the upregulated expression of NLRP3, ASC, Caspase-1, GSDMD, IL-1β, and IL-6. However, the expression of these proteins was suppressed after removing ROS or NLRP3. In addition, we found increased expression of TLR4 and NF-κB responsible for silica recognition and pyroptosis priming after silica exposure. For in vivo studies, we established animal model by intratracheally instilling 5 mg of silica into mice with/without NLRP3 inhibition. Four weeks later, we found diffused infiltration of inflammatory cells and enhanced collagen hyperplasia partially reversed by additional treatment with MCC950, so as the expression of pyroptotic molecules and proinflammatory cytokines. In particular, the dual immunofluorescent staining showed co-expression of macrophage-specific biomarker F4/80 and NLRP3 within the cells, and silica of nano-size showed more potent toxicity and pathogenicity than that of the micro size particles both in vitro and in vivo. To sum up, macrophage pyroptosis is an upstream event of silica-induced pulmonary inflammation promoted by ROS through the TLR4/NLRP3/NF-κB signaling axis.